TELAAH TENTANG TARI BENTEN (The Study of Benten Dance) - Efrida Efrida (Greget, 2009)
The widespread nature is a teacher. That term becomes the philosophy of life of the Minangkabau society which finally inspires them in expressing their art life. One of the works of art of Minangkabau artists which is inspired by the natural phenomenon and expressed in the form of dance is Benten Dance. Inspired by a flying eagle rotating motion – turn in the blue sky while stalking its prey, Benten dance symbolize the meaning of love of a mother in taking care of her child. This is in accordance with matrilineal custom Minangkabau society that puts women at the main place in society. In addition, Benten dance moves is also based on silat moves (Indonesian martial art), which if it is described consist of motifs of moves, movement phrases, sentence or kinds of moves and parts of moves. Keyword : Benten Dance